STRESS-STRAIN STATE OF SATURATED LANDSLIDE SUBJECTED TO GRAVITATION FORCES - Lavrenyuk, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The general approach to computer simulation of behavior of natural and technogeneous systems, in particular forecast of its sliding safety, by calculating the stress-strain state of saturated ground slope subjected to gravitation forces is proposed. The governing relations for considered problem was obtained, and iteration method of stress-strain state assessment of landsliding area, that allows to solve on every step planar elasticity problem was constructed. For solving the elastic problem the modified boundary element method is used; it allows to find simultaneously all the components of stress-strain state on the boundary of examined body. The method proposed allows for prescribed external loadings and saturation of landslide to determine possible zones of plasticity within the landsliding area.